On Jan Łukasiewicz's 'The Principle of Contradiction and Symbolic Logic'. Issue 2 (2nd April 2020) - Trybus, Adam; Linsky, Bernard
Abstract : This is a companion article to the translation of 'Zasada sprzeczności a logika symboliczna', the appendix on symbolic logic of Jan Łukasiewicz's 1910 book O zasadzie sprzeczności u Arytotelesa ( On the Principle of Contradiction in Aristotle ). While the appendix closely follows Couturat's 1905 book L'algebra de la logique ( The Algebra of Logic ), footnotes show that Łukasiewicz was aware of the work of Peirce, Huntington and Russell (before Principia Mathematica ). This appendix was influential in the development of the Polish school of logic, directly inspiring Stanisław Leśniewski and Leon Chwistek and more widely by serving as a text of the new symbolic logic. This appendix was an important source of the dominant algebraic logic in Poland, but also indicates that Łukasiewicz appreciated Russell's axiomatic approach to logic.